Association Between Serum Levels of Neurofilament Light Chains and Minimal Hepatic Encephalopathy in Patients With Liver Cirrhosis. Issue 10 (19th October 2021) - Labenz, Christian; Nagel, Michael; Kämper, Paula; Engel, Sinah; Bittner, Stefan; Kaps, Leonard; Galle, Peter R.; Schattenberg, Jörn M.; Wörns, Marcus-Alexander; Lüssi, Felix
Abstract : INTRODUCTION: Serum biomarkers for the diagnosis of minimal hepatic encephalopathy (MHE) in patients with liver cirrhosis would be desirable. In this proof-of-concept study, we investigated the association between MHE and serum levels of neurofilament light chains (sNfL) in patients with liver cirrhosis. METHODS: sNfL were studied in patients with liver cirrhosis (with or without MHE) and controls (patients with ischemic stroke, transitory ischemic attack, and healthy individuals). MHE was diagnosed using the Psychometric Hepatic Encephalopathy Score. RESULTS: Patients with MHE showed higher sNfL than patients without MHE and controls. In multivariable analyses, higher sNfL were independently associated with the presence of MHE. sNfL had a reliable discriminative power for the detection of MHE with an area under the curve of 0.872. DISCUSSION: MHE is associated with higher sNfL.